Innovation and optimization of Rizatriptan Benzoate Oromucosal Tablets by Using Design of Experiment (DoE) - Sonawane, T. D.; Pawar, S.P. (Journal of Drug Delivery and Therapeutics, 2022)
The present study deals with the formulation and study of oromucosal tablets of Rizatriptan Benzoate (RB) using different bioahdesive polymer. Nine formulations were prepared by using direct compression method. Hydroxypropyl methyl cellulose (HPMC K4M), Gum acacia and Sodium Alginate were used as buccal mucoadhesive polymer. Ethyl cellulose (EC) used as an impermeable backing layer. FTIR Studies showed no interaction with drug, polymer and excipients. 32 full factorial design was used to optimize the effect of independent variable such as concentration of HPMC K4M (X1) and concentration of Sodium Alginate (X2) on dependent variables such as % drug release (Y1), Mucoadhesive strength (Y2), Swelling Index (Y3). The prepared buccal mucoadhesive tablets were evaluated for weight variation, Hardness, Surface pH and drug content, content uniformity, swelling index, In-vitro drug release study and mucoadhesive strength. In-vitro drug release study showed sustained drug released for 9 hours. The In-vitro release kinetics reveals that formulation DE5 follows Higuchi model for drug release. Keywords: Buccal Mucoadhesion, HPMC K4M, Sodium alginate, Design of experiments.